Toxoplasma gondii infection and toxoplasmosis in North Africa: a review - (:unkn) unknown (My University, 2019)
Toxoplasmosis is an important zoonosis caused by an obligate intracellular parasitic protozoan, Toxoplasma gondii. The disease is distributed worldwide and can affect all warm-blooded vertebrates, including humans. The present review aimed to collect, compile and summarize the data on the prevalence of T. gondii infection in humans and animals in the five North African countries (Morocco, Algeria, Tunisia, Libya and Egypt). Published data from national and international databases were used. Distribution patterns and risk factors for T. gondii infection are discussed, focusing on biotic and abiotic factors. This review is a comprehensive epidemiological analysis of T. gondii infection in North Africa and will therefore be a useful tool for researchers. It can also be used to propose or enhance appropriate national toxoplasmosis control programs.
Keywords: African Research